THE ROLE OF PUBLIC-PRIVATE PARTNERSHIP IN THE FINANCIAL MECHANISM OF ACTIVATING HOUSING CONSTRUCTION IN THE CONDITIONS OF THE FORMATION OF A SOCIAL ECONOMY - Світлана Тульчинська; Ростислав Тульчинський; Олена Костюнік (Економіка та суспільство)
The article examines the role of public-private partnership in the financial mechanism for activating housing construction in the context of the formation of a social economy.The principles of the social economy have been clarified and its relationship with the financial mechanism for activating housing construction has been determined. A study has been conducted to determine the essence of the concept of "social economy". The advantages of activating public-private partnership in the financial mechanism for housing construction have been determined, which makes it possible to provide a larger number of people with housing that meets the goals of the social economy. To encourage business to participate in housing construction projects, the state should use various levers and methods within the financial mechanism to reduce project risks.